PENGARUH PRAKTIK CORPORATE GOVERNANCE TERHADAP BESARAN TRANSAKSI PIHAK BERELASI DAN KINERJA KEUANGAN PERUSAHAAN - HERLIANA, VINA (Jurnal Akuntansi AKUNESA, 2018)
This research aims to determine the effect of Corporate Governance practices on the magnitude of Related Party Transactions (RPT) and financial performance listed on the Indonesia Stock Exchange (IDX). This research used manufacturing companies with concentrated share ownership in the 2012 ? 2016 period as a research sample and uses the MANOVA test, these resulst indicate that the practice of Corporate Governance does not affect the magnitude of Related Party Transactions. Besides that, the practice of Corporate Governance affects financial performance.Keywords: Corporate Governance, Related Party Transactions, Financial Performance